(3QSGdI HgG CfSGH hQShe HYV GdCTQGas
(3ChdgG (B:s
(3GdMeO ddg, hLO HNW Gdabjg SjOi YHOGddg Hf RjGf CMO YOhd GdfbjH SjOi YHOGdbGOQ Hf QShe GdCTQGa SfI KeGfjf hCda aj hQbI ajgG s
(3BNQgG (B:s
(3GdYQHi Hf YjGO GdMeGd, SjOi CMeO Hf SYjO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B283 - (3U(B285s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B194 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B487) s
Keywords: (3GdJGQjNs